Mukbang Live Streaming Commerce and Green Agri-Food Products Consumption: Exploring the New Dynamics of Consumer Purchasing Decisions - Xinqiang Chen; Jiangjie Chen; Zhiwen Cai (Agriculture)
China’s live streaming boom has led to mukbang live streaming as a unique food marketing tool. Hosts interact with viewers by tasting and showcasing diverse cuisines in real time. This form of mukbang live streaming has recently been utilized to promote and sell green agri-food products. However, in-depth research into how mukbang live streaming affects the purchase intention for green agri-food products and the underlying mechanisms remains scant. We developed a theoretical model based on stimuli–organism–response theory to explore the impact mechanism. Data was collected via a survey of 455 users from agriculture-related live streaming platforms and analyzed using structural equation modeling with partial least squares. The study found that professional recommendation, audiovisual experience, and social interaction enhance consumers’ perceived utilitarian value; green advocacy, audiovisual experience, and social interaction positively affect consumers’ perceived social value. Both perceived utilitarian value and perceived social value positively affect the intention to purchase green agri-food products. Additionally, we used importance-performance map analysis to compare the model’s effects with latent variable averages, revealing each factor’s importance and performance. The findings offer new insights and recommendations for agri-food marketing strategies, particularly in enhancing consumer behaviors towards green agri-food products, aiding suppliers and mukbang live streaming platforms in more effectively promoting these products.